Hadis perspektif shi'ah - Luaili, Anjaliyatul; Safitri, Rosa (Yayasan Penelitian Dan Pengabdian Masyarakat Sisi Indonesia, 2025)
Islam is the only religion that is on the side of Allah SWT. Which in the process of spreading it Allah sent a messenger named Muhammad saw, at the beginning of the spread of Islam Allah ordered him to spread Islam or preach secretly, until finally the Messenger of Allah was ordered to preach openly. Islam continues to grow, even though the Messenger of Allah saw had died. And the struggle for Islamic preaching was continued by the Khulafa` al-Rāshidīn led by Abu Bakr, ’Umar ibn al-Khaṭṭtab. ‘Uṡman ibn ‘Affan and the last ‘Ali ibn Abi Ṭalib. But who would have thought that Islam which was fought so hard by the Prophet and his companions would be divided into many divisions. The beginning of the division was marked since the leadership of the last Caliph, namely ‘Ali ibn Abi Ṭalib. And the split group was termed Shī’ah. Shī’ah is linguistically interpreted as adherents or supporters, while in terms of Shī’ah it is interpreted as a group that supports 'Ali. At first, Shī’ah was just an ordinary group that still believed in Ahl al-Sunnah, but over time this understanding began to be contaminated so that the Shī’ah group was divided and became more extreme. Since then, the development of hadith among Shī’ah began to violate Shara, even to the point of going astray.